Предмет: Алгебра,
автор: кристина0192837465
(x2+4x+1)(x2+4x+5=-4
Ответы
Автор ответа:
0
(x²+4x+1)(x²+4x+5)=-4
Пусть x²+4x+1=t ⇒
t*(t+4)=-4
t²+4t=-4
t²+4t+4=0
(t+2)²=0
t+2=0
x²+4x+1+2=0
x²+4x+3=0 D=4
x₁=-1 x₂=-3
Ответ: x₁=-1 x₂=-3.
Пусть x²+4x+1=t ⇒
t*(t+4)=-4
t²+4t=-4
t²+4t+4=0
(t+2)²=0
t+2=0
x²+4x+1+2=0
x²+4x+3=0 D=4
x₁=-1 x₂=-3
Ответ: x₁=-1 x₂=-3.
Похожие вопросы
Предмет: Литература,
автор: elnurziyavdinov2002
Предмет: Физкультура и спорт,
автор: alinabulbas463
Предмет: Информатика,
автор: egorvv12334
Предмет: Математика,
автор: dengin2004
Предмет: Математика,
автор: юля733